Indigenous traditional practices for eco-friendly management of insect/pest in Maharashtra, India - Sharma, P P; Sawant, R J (Recent Research in Science and Technology, 2012)
An ethnobotanical study on plants used for indigenous traditional management of insects pests by people in Maharashtra was conducted to document the information particularly associated with the use as insecticide and pesticide potential of plants. In this study, following areas from the Maharastra were worked out, Ratnagiri, Raigad and Sindhudurg of Konkan, Toranmal and Dhadgaon areas in Nandurbar district, some areas in Nasik and Ahemdnagar districts. People residing in the villages and nearby forests depends mostly on traditional management of household insects, pests through their own methods use different plants, plant parts, etc. The present paper deals with the plants used to control insects and pests by the people of Maharashtra. A total of 84 plants belonging to 40 families have been documented for their insecticidal/pesticidal potential. Of these, families with more number of species used as insecticide or pesticide are, Fabaceae with 10 species; Lamiaceae with 8 species; Euphorbiaceae with 6 and Asteraceae with 5 species.